THE CONCEPT OF HUMAN CAPITAL FORMATION AT TRADE ENTERPRISES IN THE PARADIGM OF INDUSTRY 5.0 - SHKURENKO, Olga (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article proves the key role of human capital and states that it is man as a carrier of values, knowledge, experience and potential that is the basis, partner of all management, educational, technological and organizational processes. It is stated that the industry 5.0 influences the change in the requirements for the qualification of employees, new models of motivation are formed, the role of emotional intelligence, adaptability and ability to interdisciplinary interaction is increasing. The role of trade companies in the global supply chains has been proven and that the efficiency of their functioning is increasingly dependent on the quality, adaptability and innovative potential of human capital. In conditions of economic instability, hostilities, violation of supply chains, digital transformations, human capital itself is a key source of organizational flexibility, adaptability and stability of trade enterprises. The principles of formation of human capital at trade enterprises, which include strategic, investment, innovation, continuity, adaptability, flexibility, motivational synergy, digitalization are systematized. These principles are the basis for developing an effective mechanism for managing human capital of trade enterprises, which allows you to develop, motivate and maintain talented employees, ensuring the achievement of strategic goals. Modern tools for the formation of human capital at trade enterprises in industry 5.0 are generalized and offered. These include personalized learning and development, digital management mechanisms, development of emotional intelligence and Soft Skills, integration with sustainable development strategies. They are multifunctional mechanisms, the introduction of which contributes to the successful strategic development of trade enterprises with the involvement of highly skilled personnel.